Risk Factors of Small Intestine Cancer: An Epidemiological Analysis and Their Role in Early Diagnosis - A Literature Review - Miklis, Paweł; Pniak, Michał; Mawlichanów, Maciej; Różycki, Adrian; Wojtczak, Marta; Szerej, Krzysztof; Ciesielska, Aleksandra; Myśliwiec, Natalia; Sieradzka, Aleksandra; Kot, Alicja (Quality in Sport, 2025)
Introduction: Small intestinal cancer is a rare form of cancer affecting the duodenum, jejunum, or ileum. Its incidence is increasing, although it is less commonly diagnosed than colorectal cancers. Understanding risk factors is crucial for early detection and prevention. These factors include non-modifiable ones like sex, race, age, and genetic conditions, as well as modifiable factors like diet, alcohol, smoking, and obesity. Materials and Methods: A search of PubMed with the keywords "small intestine cancer" and "risk factors" identified 928 articles. After review, 48 publications and one textbook, were included. Results: Small intestine cancer is more common in men and African Americans. Genetic conditions such as Lynch syndrome, Familial Adenomatous Polyposis (FAP), Peutz-Jeghers syndrome (PJS), and Multiple Endocrine Neoplasia (MEN1) significantly increase the risk. Chronic conditions like Crohn’s disease and celiac disease also increase risk. Diets high in red meats, processed foods, and animal fats, are linked to higher risk. Discussion: Age and sex are key non-modifiable risk factors, with risk increasing with age, particularly over 60. Genetic conditions like Lynch syndrome, FAP, and PJS are major contributors. Chronic inflammatory diseases such as Crohn’s and celiac disease raise risk. Diets rich in animal fats, processed meats, and smoking contribute to higher risks, as does obesity. Healthy diet, quitting smoking, and maintaining a healthy weight, may reduce risk. Conclusion: Genetic mutations, such as those in Lynch syndrome, FAP, and PJS, are significant risk factors, while lifestyle factors like diet, smoking, and obesity also play a role. Increased surveillance for individuals with genetic predispositions or inflammatory conditions may allow for earlier detection. Despite limited data, a balanced diet, weight management, and avoiding smoking may help reduce risk. Further research is needed to improve prevention strategies.